A Case of Postpartum Takotsubo (Stress) Cardiomyopathy. (4th August 2022) - Kandah, Fadi; Deol, Tanya; Dhruva, Pooja; Chandler, Zachary; Musa, Thaer; Velarde, Gladys
Abstract : Takotsubo (stress) cardiomyopathy (TCM) is usually triggered by psychological and/or physical stress. Most often, it is seen in postmenopausal women. Cases of TCM related to pregnancy are rare. We present a unique case of a 35-year-old, two-day postpartum female who was diagnosed with TCM.